Strengthening Environmental Awareness Among Elementary School Students Through The Use of Tumblers - Riska Ramadhani; Irina Safitri Zein; Wilda Rahmi; Nurul Hayati; Ikhsan Muhammad Iqbal; Elly Susanti (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
The increasingly uncontrollable issue of plastic waste has captured people's attention. Instilling environmental awareness from an early age is crucial to prevent this problem from being passed down to future generations. This community service program aims to educate students about the importance of environmental preservation and to raise awareness of the dangers posed by non-biodegradable plastic waste. This activity invites students to replace bottled water with reusable tumblers as a practical solution. The socialization activity on the use of tumblers to reduce plastic waste was conducted on November 11, 2024, SDN No. 57 Banda Aceh. Prior to this session, some students already had a basic understanding of plastic waste and its environmental impacts. Positive habits, such as bringing their own tumblers to school instead of purchasing bottled beverages, had already been adopted by a number of students. The event was carried out smoothly and received a highly positive response from the sixth-grade students of SDN 57 Banda Aceh. The students were enthusiastic throughout the entire session and provided excellent feedback during the discussions. Motivational rewards further encouraged students to actively participate in the socialization and pay close attention to the material presented.